Gamification teaching in mathematics subject as a guide for future teaching and learning - Yiling, Liu; Razali, Fazilah (Human Resource Management Academic Research Society, 2023)
The study aimed to determine the practical application of gamification in real-life mathematics classrooms in lower primary schools in China and students' satisfaction with gamification in mathematics classrooms. A total of 141 students from the lower grades (grades 1-3) of Chinese public primary schools participated in the survey and quantitative data were collected through the Student Evaluation of Educational Quality (SEEQ) form. Eight areas were assessed using the five-point Likert-type scale: (1) Learning (2) Enthusiasm (3) Organisation (4) Interaction (5) Breadth of Coverage (6) Examinations/ Grading (7) Assignments (8) Workload/Difficulty. The relationship between gender and interest in learning mathematics was analyzed using a t-test. The results of the study show that students are more satisfied with gamified teaching and that gender affects the interest in mathematics learning (in favor of males). In conclusion, gamified teaching is better used in practice in the mathematics classroom of lower grades in Chinese public primary schools, with higher levels of student satisfaction.